Politik Uang Dalam Pemilu-Pemilukada 2014: Modus dan Resolusinya - Zuly Qodir (Institut Pemerintahan Dalam Negeri (IPDN), 2016)
This paper exposes the onset of political money in the elections which took place in Indonesia. Increasingly sophisticated in money politics operate. Mode of vary from giving gifts, give dorprize, give pocket money when the election took place, promises to be an employee up to deliver the promise of delivering the project. The perpetrators of political money is not alone among politicians’ central level, but going from the central level to district level. Political money so lively it is, like a fart, so called by the fart politics, often very foul-smelling, even sound but never caught the whodunit. The organizers of the election, in this case the Electoral (ELECTION COMMISSION) cannot give sanctions lay off the perpetrators of money politics, even Bodyguard of Election (Bawaslu) also can not rebuked him. That is the political movement of money that continue to occur in every Election but always failed to be removed. This paper then offers alternative solution i.e. with disqualification for the perpetrators of political money to participate in the elections while known practicing while the next election are prohibited from participated and competed.